2014
DOI: 10.1590/s0366-69132014000200018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volcanic tuff on the characteristics of cement mortar

Abstract: This paper examines how Jordanian volcanic tuff aggregates affect the characteristics of cement mortar. Five mortar mixes were prepared by replacing normal aggregate (standard sand) with volcanic tuff aggregate in ratios of 0, 25, 50, 75, and 100% (M1 to M5, respectively). Compressive strength, flexural strength, and unit weight were tested at mortar ages of 3, 7, 28, and 56 days. The results revealed improved compressive and flexural strength, which were maximal for the M3 sample. Unit weight decreased as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Other problems have been seen in the production process of companies that focus on technological properties [ 13 ] rather than on the intrinsic characteristics of these materials [ 14 , 15 , 16 , 17 ]. The use of tuff as a pozzolan has increased in recent decades in many parts of the world [ 18 , 19 , 20 , 21 , 22 ], with well-known results. Volcanic tuffs can match and outperform other minerals and industrial rocks, such as zeolites, bentonites, perlites, pumicites, trachytes, rhyolites and kaolinites [ 23 , 24 , 25 , 26 , 27 , 28 ], with regards to their cementing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Other problems have been seen in the production process of companies that focus on technological properties [ 13 ] rather than on the intrinsic characteristics of these materials [ 14 , 15 , 16 , 17 ]. The use of tuff as a pozzolan has increased in recent decades in many parts of the world [ 18 , 19 , 20 , 21 , 22 ], with well-known results. Volcanic tuffs can match and outperform other minerals and industrial rocks, such as zeolites, bentonites, perlites, pumicites, trachytes, rhyolites and kaolinites [ 23 , 24 , 25 , 26 , 27 , 28 ], with regards to their cementing properties.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that replacing 20% of fine aggregate with brown or grey tuff improved the concrete compressive strength by 10%, and 15% when yellow tuff was used. Al-Zou’by et al [ 17 ] investigated the impact of replacing sand with different levels of tuff replacement (25%, 50%, 75%, and 100% by weight) on concrete. Their results showed that the compressive and flexural strengths of samples containing 50% tuff increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate an increase in absorption with the increase of temperature and percentage of replacement of VA at 28 days age, except for the higher temperature case (500 and 800°C) where the control specimens exhibit the maximum absorption. Heating the specimen would increase the rate of absorption, as the water within the concrete would start evaporating after 100 °C [30]. The water within the hydrated cement can be classified into two categories; the evaporable water (water in the capillary pores and some water in the gel pores) and Non-evaporable water (nearly all chemically combined water and some water not held by chemical bonds) [18].…”
Section: Absorptionmentioning
confidence: 99%